How Islamic Psychospiritual Contribute To Balanced Mental Health And Human Wellbeing - Khatijah Othman; Muhamadul Bakir Yaakub; Nur Fatinni Mohamad Kamal; Amin Al Haadi Shafie (Journal of Posthumanism, 2026)
Non-Indexed Publication